Antecedents Of Competence, Digital Learning and The Influence On Teacher Performance of Senior High School - Marbawi, Marbawi; Hamdiah, Hamdiah; Nurmala, Nurmala (International Journal of Engineering, Science and Information Technology, 2022)
This study aims to determine two antecedent variables of competence, digital learning, and the impact on teacher performance of senior high school Aceh Province. The data is used by distributing questionnaires to 180 respondents of teacher old high school Aceh Province. The data source is primary, the dissemination of questionnaires to respondents; the data collection technique used in this study uses questionnaires is a series of submitted written questions and disseminated to respondents to get answers in writing from the teacher senior high school Aceh Province. The statistical analysis used structural equation modeling and was processed with the help of the application Amos to analyze the data. In this study, the authors use the structural equation model method to test hypotheses; the structural equation model is a set of statistical techniques that allows the simultaneous testing of a relatively complex series of relationships. What is meant by complicated is that simultaneous models are formed through more than one dependent variable simultaneously acting as independent variables for other tiered relationships. The variables measured include digital leadership effect toward competence and digital learning. Then an analysis of statistical test is digital leadership, competence, and digital learning effect toward senior high school Aceh Province. The resulting job satisfaction variable effect of partial mediated on work characteristics toward to apparatus Performance of Â National Narcotics Agency Aceh Province.